Regional cerebellar volume reflects static balance in elite female short-track speed skaters - Park, I. S.; Yoon, J.-h.; Kim, N.; Rhyu, I. J. (International Journal of Sports Medicine, 2013)
The cerebellum plays a critical role in balance control. Particularly, elite short-track speed skaters require fine postural control to keep a postural balance during high velocity movement across smooth ice. We investigated whether skating proficiency and gender have an effect on the volume of cerebellar subregions and static balance, using 3-dimensional magnetic resonance imaging volumetry. In addition, we further analyzed which subregions of the cerebellum correlates with the balance. The volumes of cerebellar subregions and static balance index were compared among 12 male and 11 female elite short-track speed skaters, and 11 male and 14 female healthy matched subjects. We found significant main effects of skating proficiency and gender on the volume of vermian lobule VI-VII (declive, folium, and tuber), short-track speed skaters having greater volume than control and women revealing greater volume than men. Especially, in female athletic group, the volume of vermian lobule VI-VII significantly correlates with left static balance. In addition, men showed larger skating proficiency-related differences than women in the performance of static balance. The correlation between the volume of this region and static balance in female short-track speed skaters suggests that this region would plays a critical role in balance.